Alcohols as alternative fuels in compression ignition engines for sustainable transportation: a review. Issue 4 (21st December 2022) - Sahu, Tomesh Kumar; Shukla, Pravesh Chandra; Belgiorno, Giacomo; Maurya, Rakesh Kumar
ABSTRACT: Alcohol fuels, primarily ethanol and methanol, have emerged as one of the important alternatives for sustainable transportation and power generation applications, due to the overall lower carbon dioxide (CO2 ) emissions. The higher octane number of alcohol makes it suitable for spark ignition (SI) engines while lower blend ratios can be used for compression ignition (CI) engines as well. Since significant work and exploration have already been performed for the application of alcohol in SI engines, the present study is primarily focused on alcohol utilization in CI engines. This review majorly consists of three parts: first, a discussion on the physical and chemical properties of ethanol and methanol from the fuel perspective, second, combustion, and engine performance of CI engines fueled with alcohol and lastly, emissions characterization of alcohol as fuel. A summary of this review is provided which highlights the potential of alcohol utilization in the form of blend or under dual-fuel combustion modes, as well as neat alcohol fueled CI engine. Alcohol-fueled CI engine improves the soot-NOx trade-off characteristic in comparison to conventional diesel combustion, this fuel could be an enabler to meet future emissions regulations. Overall lower CO2 emissions (up to 15% lower compared to diesel) by utilizing alcohol as fuel make it suitable for sustainable transportation.